Evaluating the impact of a brief Health at Every Size-informed health promotion activity on body positivity and internalized weight-based oppression - Lily, O’Hara (2021)
Weight-based oppression, including negative attitudes about body weight, and harassment, stigma, and discrimination based on body weight, is a widespread phenomenon that leads to considerable distress and poor health and wellbeing outcomes. Conversely, body positivity is a multi-faceted concept that encompasses body acceptance, body appreciation, and body love, and adaptive approaches protective of health and wellbeing. The aim of this study was to evaluate the impact of a brief health promotion activity informed by Health at Every Size- and critical health promotion principles on body positivity and internalized weight-based oppression in female students at Qatar University. A quasi-experimental mixed methods pre-post evaluation design was used, with quantitative assessment of body positivity and internalized weight-based oppression before the activity, immediately afterwards, and 10 weeks later, and qualitative assessment at the 10-week follow up. Measures used were the Body Appreciation Scale 2, Modified Weight Bias Internalization Scale, Fat Attitudes Assessment Toolkit Size Acceptance and Self Reflection on Body Acceptance subscales, and an open-ended questionnaire. Body acceptance and appreciation increased significantly after the activity. Qualitative results suggest that these improvements were sustained at follow up. Brief Health at Every Size® informed health promotion activities show potential to improve health and wellbeing.